A snowy robin rescue - Kelly, Mary (London : Scholastic, 2014)
Evan and Hannah have found a robin in the snow. It's not moving, and they soon realize that the tiny robin is stuck! They call the RSPCA and an inspector arrives to help. It's snowing heavily and they need to act fast. Can the RSPCA perform a snowy robin rescue? An exciting, inspiring story based on a real-life animal rescue. With illustrations throughout and lots of facts about robins and the RSPCA.
W
820
W
Keywords: Animals -- Fiction; Animals -- Fiction